Malaysia agricultural sector : Competitiveness in AFTA - Md. Isa, Mohd. Azwardi; Radzuan, Kamaruddin (2005)
Agriculture is a vital economic activity in Malaysia. Globalization poses threats to national industries and agribusiness in the international and domestic markets. Due to this situation, the government has given prime consideration to the agricultural sector in the 2004 budget. Even though the agricultural sector has gaining serious attention by the government, there is a question arises regarding the capability of the Malaysia agricultural sector to compete in AFTA, since its implementation also greatly affect that sector. This paper will discuss a-fetlq aspects in agriculture sector such as its present status and challenges which all these aspects will determine Malaysia competitiveness in AFTA.